The Fornax cluster VLT spectroscopic survey: I. VIMOS spectroscopy of compact stellar systems in the Fornax core region - Pota, Vincenzo; Lisker, Thorsten (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We present the results of a wide spectroscopic survey aimed at detecting extragalactic globular clusters (GCs) in the core of the Fornax cluster. Abo